2021
DOI: 10.3389/fcvm.2021.756810
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Plant-Based Diet With Cardiovascular Disease and Mortality: A Meta-Analysis and Systematic Review of Prospect Cohort Studies

Abstract: Background: The association between plant-based diets and cardiovascular disease (CVD) remains poorly characterized. Given that diet represents an important and a modifiable risk factor, this study aimed to assess (1) the relationships between the impact of adherence to plant-based diets on cardiovascular mortality, incident CVD, and stroke; (2) if associations differed by adherence to healthful and less healthful plant-based diets.Methods and Findings: MEDLINE and EMBASE databases were searched up to May 2021… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 78 publications
1
48
2
2
Order By: Relevance
“…A recent systematic review by Remde et al ( 46 ), demonstrated that PBD, in general, demonstrated improved weight control and cardiometabolic outcomes. Healthy plant-based foods play a beneficial role in lowering cardiovascular mortality and CVD according to the findings of a meta-analysis and systematic review of prospect cohort studies ( 53 ). Interestingly, another study reported that, PBD (which included Mediterranean, vegetarian, and vegan diets) improved TMAO levels, whereas animal-based diets appear to have the contrary effect ( 54 ).…”
Section: What Are Pbds?mentioning
confidence: 99%
“…A recent systematic review by Remde et al ( 46 ), demonstrated that PBD, in general, demonstrated improved weight control and cardiometabolic outcomes. Healthy plant-based foods play a beneficial role in lowering cardiovascular mortality and CVD according to the findings of a meta-analysis and systematic review of prospect cohort studies ( 53 ). Interestingly, another study reported that, PBD (which included Mediterranean, vegetarian, and vegan diets) improved TMAO levels, whereas animal-based diets appear to have the contrary effect ( 54 ).…”
Section: What Are Pbds?mentioning
confidence: 99%
“…There are several types of vegetarian diets, but all of them are characterized by the reduction or exclusion of animal meat consumption [67]. Following a balanced plantbased diet has several benefits [68]. It has been observed that the population of countries whose usual dietary model excludes the consumption of meat is less likely to develop cardiovascular diseases [67].…”
Section: Vegetarian Dietsmentioning
confidence: 99%
“…It has been observed that the population of countries whose usual dietary model excludes the consumption of meat is less likely to develop cardiovascular diseases [67]. Moreover, a plant-based diet significantly reduces the risk of death from cardiovascular causes [68]. Plant-based diets, unlike diets based on animal meat consumption, provide significant amounts of cardioprotective fiber, beta-glucans, and plant phytosterols that limit the absorption of lipids from the gastrointestinal tract.…”
Section: Vegetarian Dietsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in this study, it was green tea beverages, rice, and oolong tea beverages (84%, 7%, and 4%, respectively). Plant-based foods, a major dietary source of manganese, have already been reported to be inversely associated with cardiovascular disease 10) . Therefore, it remains possible that the results of this study are a proxy for plant-food intake rather than manganese intake.…”
Section: Fundingmentioning
confidence: 99%